Peran Dinas Sosial Dalam Upaya Pemenuhan Hak Orang Dengan Gangguan Jiwa Menurut Undang-Undang Nomor 18 Tahun 2014 Tentang Kesehatan Jiwa di Kota Kuala Tungkal - Wahyudi, Isma; Muslih, M; Supeno, Supeno (Universitas Batanghari Jambi, 2024)
Individuals with mental disorders are categorized as mentally disabled, according to the provisions of the article, individuals with mental disorders are guaranteed their rights to receive special care and assistance at the expense of the State to ensure a decent life in accordance with their human dignity. The objectives of this research are: 1) To understand and analyze the role of the Department of Social Affairs in efforts to fulfill the rights of People with Mental Disorders according to Law Number 18 of 2014 concerning Mental Health in the City of Kuala Tungkal. 2) To understand and analyze the obstacles in the implementation of the role of the Department of Social Affairs in efforts to fulfill the rights of People with Mental Disorders according to Law Number 18 of 2014 concerning Mental Health. 3) To understand and analyze the efforts made by the Department of Social Affairs in efforts to fulfill the rights of People with Mental Disorders according to Law Number 18 of 2014 concerning Mental Health.